Les pouvoirs de légiférer en matière de langue après la « Loi constitutionnelle de 1982 » - Pelletier, Benoît (Les Cahiers de droit, 1984)
The object of this study is to ascertain the power of the federal and the provincial governments to legislate concerning language in Canada. After a study of the ancillary doctrine as the constitutional basis for the exercise of this power by either level of government, the author studied the constitutional restrictions on its use, and determined the following restrictions : 1. For the federal government and the government of the province of Quebec, only : section 133 of the Constitution Act, 1867 which is also an entrenched provision providing minimum rights. 2. For the province of Manitoba only : section 23 of the Manitoba Act, 1870 which is also an entrenched provision providing minimum rights. 3. For the province of New-Brunswick, only : sections 16(2), 17(2), 18(2), 19(2) and 20(2) of the Constitution Act, 1982. 4. For all provinces, subject to the present inapplicability of section 23(1) a) of the new charter concerning the province of Quebec : section 23 of the Constitution Act, 1982. 5. For all provinces and for the federal government : section 16(3) of the Constitution Act, 1982, section 15(1) which recognizes the right to equality, and 2b) which recognizes the freedom of expression. Finally the author studied the implications of the reasonable limits' provision outlined in section 1 of the new charter, this constituting the only means for our governments to avoid the application of the charter to their legislation.